Peran Guru Kristen Dalam Meningkatkan Kedisiplinan Di SD Tiga Bahasa Rukun Harapan Jember - Dari Jernih Mendrofa (Sekolah Tinggi Teologi Duta Panisal, 2020)
Education is one of the main needs in increasing the potential of quality nation children. Various participation from families and communities also provide support for the development of potential in education, which can advance the quality of education inIndonesia for the better. In developing education, namely the development of children's character and morals is the responsibility of all parties. family environment, community environment and school environment. In the family environment, the child first receiveseducation from parents. In the community that occurs outside the family. Whereas in the school environment is a teacher. Rules are provisions that have been set to govern the behavior of a person in a group, organization, institution, or community. Schoolregulations aim at peace, harmony within the school environment. Discipline directs one's behavior in a positive direction. The method is to use a Case Study approach, which is a detailed and in-depth data collection involving various sources of information. With discipline will help the course of education, solve existing problems properly and if not disciplined it will hamper the education process. Therefore discipline is a way to help students to develop self-control and be able to shape behavior in a positive direction.